Thiol reactive polymers and hydrogels - Kosif, İrem. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Synthesis of polymers and hydrogels with reactive side chains has attracted considerable attention since these polymers are widely utilized in bioconjugation. We have recently introduced the synthesis of polymers decorated with maleimide units as ‘reactive’ functional groups utilizing of a novel methacrylate monomer which accommodates a masked maleimide functionality. This thesis expands on the polimerizations of this abovementioned monomer. Since the synthesis of such reactive polymers with narrow molecular weight distributions is desirable for many applications, Atom Transfer Radical Polymerization (ATRP) has been employed to obtain such polymers. Poly (ethylene glycol) (PEG) based polymers are known to be non-immunogenic and biocompatible and are promising candidates for formulation of polymer-drug conjugates. As one part of this study, water soluble PEG methacrylate based copolymers that contain thiol reactive maleimide side chains have been synthesized using ATRP. The maleimide groups are directly incorporated during the polymerization using a furan protected maleimide containing monomer. After the polymerization, the maleimide groups can be activated to their reactive form to furnish the thiol reactive copolymers. The maleimide side chain containing polymer can be efficiently derivatized by any thiol containing molecule under mild, reagent free aqueous conditions. Hydrogels are used in a wide variety of areas such as biomolecular immobilization, tissue engineering, sensors, implant coatings, and drug delivery. Such increased interest also necessitates synthesis of novel hydrogel materials to widen the scope of intended applications of such materials. With this motivation, PEG methacrylate based hydrogels containing thiol reactive maleimide functional groups directly incorporated into the hydrogel have been synthesized. During the polymerization, the thermal deprotection of the maleimide groups in some of the monomers resulted in the formation of an in situ crosslinker. After gelation, the remaining protected maleimide groups could be activated to their reactive forms via a thermal activation step. The successful incorporation of maleimide groups and covalent functionalization of the hydrogel were investigated using fluorescent labeling with thiol containing dye molecules and enzymes.
Keywords: Thiols.; Reactive polymers.; Diels-Alder reaction.